Strategi Pemerintah Desa Jubung dalam Mendukung Program SUKA PIKNIK sebagai Upaya Penurunan Stunting - Nur Halimah, Indah Rachma; Edo Wahyudi, Kalvin (Jurnal Administrasi Publik dan Bisnis, 2026)
Stunting is still an important problem in health development in Indonesia that requires government attention at the regional level, as stated in the Minister of Health Regulation Number 10 of 2018. Jubung Village seeks to deal with stunting through support for the SUKA PIKNIK (Sukorambi Ready for Mobile Health Integration Services) program initiated by the Sukorambi District Government, which focuses on mobile health services in the form of nutrition screening and early detection of stunting cases. This study aims to analyze the strategy of the Jubung Village Government in supporting the implementation of the program using Geoff Mulgan's strategic framework. The research method uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results showed that the strategy was well implemented, demonstrated by clarity of objectives, institutional support, structured coordination, adaptive nutrition interventions, and continuous evaluation. Despite facing obstacles to regeneration of young cadres and resistance from a small part of the community, this strategy is still consistently implemented in efforts to reduce stunting.